Spintronics with individual metal-organic molecules - Schmaus, Stefan (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2011)
In this work two ideas of using individual metal organic molecules in applications for data storage are presented. On the one hand, metal-free phthalocyanine is used to form a GMR contact consisting of one single molecule leading to the world smallest magnetic sensor. On the other hand, chromium acetylacetonate was used to study the properties of magnetic molecules adsorbed on surfaces in order to build magnetic bits for date storage.